Ensino médio: concepção docente em uma escola no município de Abaetetuba-PA - ALVES, Simôní Paixão (2019)
The work presents some reflections on the educational policies for high school under the optics of teachers in the municipality of Abaetetuba in the state Pará. Initially we will take a historical approach to high school in Brazil, which presents us the moment that was instituted and its purposes, we will also present the reflections of the teachers interviewed, their conceptions about high school and the policies Developed by the state of Pará. The research is of qualitative nature, using the following instruments of data collection: semi-structured interviews, questionnaires and focal group with the high school teachers of the state Education network. This work is the result of the research carried out by the GEPESEED research group, in order to understand how educational policies are being developed in the municipality and the contributions that developed studies can bring to that level of Teaching. The authors studied were Nascimento (2015), Krawczyk (2014). The research results show that gaps in these policies tend to leave high school fragile, failing to meet their goals, leading to low performance in evaluations.